Impact of Pulsed Direct Current on Embryos, Larvae, and Young Juveniles of Atlantic Cod and its Implications for Electrotrawling of Brown Shrimp. Issue 1 (24th April 2017) - Desender, Marieke; Decostere, Annemie; Adriaens, Dominique; Duchateau, Luc; Mortensen, Atle; Polet, Hans; Puvanendran, Velmurugu; Verschueren, Bart; Chiers, Koen
Abstract: The application of electrical pulses in fishing gear is considered a promising option to increase the sustainability of demersal trawl fisheries. In the electrotrawl fishery for brown shrimp Crangon crangon, an electrical field selectively induces a startle response in the shrimp. Other benthic organisms remain mainly on the seafloor and escape underneath a hovering trawl. Previous experiments have indicated that this pulse has no short‐term major harmful effects on adult fish and invertebrates. However, the impact on young marine life stages is still unknown. Because brown shrimp are caught in shallow coastal zones and estuaries, which serve as important nurseries or spawning areas for a wide range of marine species, electrotrawling on these grounds could harm embryos, larvae, and juveniles. We carried out experiments with different developmental stages of Atlantic Cod Gadus morhua, which are considered vulnerable to electrical pulses. Three embryonic stages, four larval stages, and one juvenile stage of Atlantic Cod were exposed to a homogeneous electrical field of 150 Vpeak /m for 5 s, mimicking a worst‐case scenario. We detected no significant differences in embryo mortality rate between control and exposed groups. However, for the embryonic stage exposed at 18 d postfertilization, the initial hatching rate was lower. Larvae that were exposed at 2 and 26 d posthatch exhibited higher mortality rates than the corresponding nonexposed control groups. In the other larval and juvenile stages, no short‐term impact of exposure on survival was observed. Morphometric analysis of larvae and juveniles revealed no differences in measurements or deformations of the yolk, notochord, eye, or head. Although exposure to a worst‐case electrical field did not impact survival or development for six of the eight young life stages of Atlantic Cod, the observed delayed hatching rate and decreased survival for larvae might indicate an impact of electric pulses and warrant further research.